m6A Regulator-Mediated Methylation Modification Patterns and Tumor Microenvironment Infiltration Characterization in Acute Myeloid Leukemia - Du, Ashuai; Wu, Xin; Gao, Yunmei; Jiang, Baili; Wang, Jianlong; Zhang, Pan; Zhao, Qiangqiang (Frontiers in Immunology, 2021)
Recent studies have demonstrated epigenetic regulation of immune responses. Nevertheless, the underlying effect of RNA N6-methyladenosine (m6A) modifications on tumor microenvironment cell infiltration remains elusive. In this study, we thoroughly assessed m6A modification patterns of 255 myeloid leukemia specimens based on 23 m6A regulators. Consensus clustering of the 23 m6A regulators was performed to determine three distinct m6A modification patterns that were remarkably consistent with three immunophenotypes of tumors: immunorejection, immune activation, and immune inertness. Further evaluation and prognostic analysis of the m6A modification patterns of individual tumors revealed that low m6A score was characterized by increased mutational burden, immune activation, and survival rates, whereas high m6A score was characterized by poorer survival rates and the absence of effective immune infiltration. In addition, this study investigated the association between m6A regulators and antitumor immune responses and discovered higher expression of the immune regulators PD-L1, PD-L2, MRP1, and MRP2 in low m6A scores. Generally, the expression pattern of m6A regulators was remarkably associated with prognostic results and antitumor immune responses in acute myeloid leukemia and may be an underlying target and biological marker for immune therapies.